RESULTS OF OUTPATIENT PROGRAM ON EFFECTIVE THERAPY OF REFRACTORY ARTERIAL HYPERTENSION - M. M. Batyushin; I. V. Derevyankina; M. Z. Gasanov; O. V. Akopova; K. I. Babiyan; Y. N. Boychenko; N. V. Vasilchenko; T. A. Gabysyan; S. Ch. Gayboryan; I. S. Golovatenko; N. M. Demkova; D. O. Dmitriev; et al. (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To increase in efficacy of antihypertensive therapy in patients with refractory arterial hypertension (HT).Material and methods. Patients with refractory HT were revealed during first month of program. The causes of refractory HT were analyzed. Combined antihypertensive therapy was prescribed to reach target level of blood pressure (BP). This therapy lasted 24 weeks and included angiotensin converting enzyme (ACE) inhibitor, thiazid diuretic (indapamide) and dihydropyridine calcium antagonist (nifedipine XL).Results. 200 patients with refractory HT were revealed. True refractory HT took place in 59,9% of patients and pseudo refractory HT – in 40,1% of patients. Lack of diuretics or combined antihypertensive therapy were the main reason of insufficient BP control. Proposed 3-drugs therapy resulted in reduction of systolic BP from 190 to 132 Hg mm and diastolic BP from 104 to 81 Hg mm. Target level of BP was reached in 94% patients. There were no side effects which demanded to stop therapy.Conclusion. High incidence of pseudorefractory HT (40,1%) is revealed. Significant prevalence of renal disturbances especially chronic interstitial inflammatory could be responsible for refractory HT development. Use of 3-drugs therapy (ACE inhibitor, indapamide and nifedipine XL) provides effective control of BP in refractory and pseudorefractory HT.